2011
DOI: 10.2174/156802611798184364
|View full text |Cite
|
Sign up to set email alerts
|

Multitarget Antithrombotic Drugs

Abstract: Thromboembolic disorders are still the leading causes of morbidity and mortality in developed societies. Therefore, prophylaxis and treatment of arterial and venous thrombosis are among the main therapeutic challenges nowadays. Simultaneous action on several targets involved in pathology of thrombosis offers potential advantages compared to existing drugs which were developed as selective modulators of single targets. The review focuses on dual inhibitors of coagulation enzymes, dual antiaggregatory compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Multitarget therapies have for many years attracted the interest of medicinal chemists in the field of complex diseases, such as cancers, inflammation, psychiatric disorders, and thrombotic disorders. These diseases can be affected by many factors, and they are often resilient to single-target treatments due to activation of compensatory mechanisms and redundant cellular pathways . Despite the many challenges of cancer therapies, current chemotherapeutics and targeted drugs can significantly prolong patient lives and in some cases also cure the disease .…”
Section: Introductionmentioning
confidence: 99%
“…Multitarget therapies have for many years attracted the interest of medicinal chemists in the field of complex diseases, such as cancers, inflammation, psychiatric disorders, and thrombotic disorders. These diseases can be affected by many factors, and they are often resilient to single-target treatments due to activation of compensatory mechanisms and redundant cellular pathways . Despite the many challenges of cancer therapies, current chemotherapeutics and targeted drugs can significantly prolong patient lives and in some cases also cure the disease .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, tissue injury and platelet activation produce a state of hypercoagulability in SCD patients [39]. In humans, antagonists of the P2Y 12 adenosine diphosphate (ADP) receptor have shown the capacity to reduce the hypercoagulability state in SCD, preventing the vaso-occlusion process [6,54]. Prasugrel, for example, decreased platelet adherence to monocytes and neutrophils, reducing the cell-platelet aggregate size [55].…”
Section: Discussionmentioning
confidence: 99%
“…Infrared (IR) spectroscopy (KBr disc) were performed on an FTIR-8300 Shimadzu spectrometer, and the frequencies are expressed per cm À1 . The nuclear magnetic resonance (NMR) for 1 H and 13 C of all compounds were scanned on a Bruker Fourier with Dual probe 13 Compounds 1, 6(a-b) and 9 were synthesized according to a previously described methodologies [18,54,59].…”
Section: Chemistry General Informationmentioning
confidence: 99%
“…Docking of the spumigin J to thrombin demonstrated that the amino group of methyllysine binds to the S1 pocket of the thrombin active site, while the (2 S ,4 S )-4-methylproline ring was bound in the hydrophobic pocket S2 and homotyrosine established the hydrophobic interactions with a hydrophobic aryl-S3 binding site [ 5 ]. Therefore, spumigins with (2 S ,4 S )-4-methylproline central core represent interesting starting compounds for the development of a new structural type of direct thrombin inhibitors [ 9 , 10 , 11 , 12 ]. Herein, we report a series of new types of direct thrombin inhibitors based on the tetrapeptide structure of spumigins, where the (2 S ,4 S )-4-methylproline central core was replaced in first series with an indoline ring as a more hydrophobic and rigid core, and in the second series of analogues with a more flexible l -proline core.…”
Section: Introductionmentioning
confidence: 99%